The American Blade: Etymologies of a Newspaper Name. (1st September 2013) - Adams, Michael
Abstract : Some American newspaper names include the element Blade, as in The Toledo Blade or The Washington Blade . One might assume that all newspaper Blades are the same, but they are, in fact, etymologically distinct, used by namers of their respective newspapers for different reasons. The residues of those etymologies figure in regional and subcultural identities, and Blade reflects various aspects of American history and culture depending on the circumstances of its use. At the finest historical scale, Blade may be a 'lexical doppelgänger, ' used in mixed communities by immigrant populations for one etymological reason, but by the established Anglo-American strata for another. While purposeful, metaphorical uses of Blade make flamboyant iconic claims about regional or subcultural identity, doppelgänger Blade is forged in the crucible or melting pot of language contact and essentially overlooked in the history of American speech.